Authoritarian Securitisation and Moral Panic: The Discourse and Role of the Senate in the 2023 Thai Election - Gregory V. Raymond (Journal of Current Southeast Asian Affairs)
In Thailand's 2023 election, an appointed Senate controlled who became prime minister. To better understand the thinking of key actors in this critical moment, this paper examines the discourse of senators who publicly commented prior to the 13 July joint sitting of the Thai parliament, where election-winning candidate Pita Limcharoenrat was blocked. This paper argues that the two predominant narratives justifying the veto, protecting Thailand's lèse-majesté law and guarding against chaos and conflict, can be analysed in four dimensions: affective, strategic, coordinative and communicative. Affectively, the narratives reflected moral panic in relation to the youth-led change in attitudes towards the monarchy. Strategically, the narratives protected elite interests via securitisation, in which a state of severe threat is invoked and used to justify extreme policies. Coordinatively, the narratives signalled to elites the costs of transgression and communicatively, they conveyed to broader Thai society the potential for conservative-sponsored street protest.